THE HUMANITY VALUES IN GUY DE MAUPASSANT’S A PIECE OF STRING AND THE IMPLICATION FOR ENGLISH LANGUAGE TEACHING - Desi Apriani (Jurnal Didascein Bahasa, 2019)
The aims of the study are to describe the humanity values found in Guy De Maupassant’s A piece of String; to describe Guy De Maupassant’s humanity in society of life atation of the indications in main characters to describe the implementation of analysis A Piece of String in ELT through literature. This research are classifies as qualitative research or used description and interpretation of the indications in main characters in the novel accurately. The libarary sources consist of primary and secondary data. The primary data was the short story and the secondary data were from books periodicals, magazines, non-printed sources on internet then data are gathered, together analyzed and finally written in description method. May The Result`of the study shows that: 1) The elements of humanity values in Piece of String follows: (1) understanding, (2) bravery, (3) togetherness, (4) cooperative, (5) honesty, (6) patience, and (7) loyalty. 2) The result is the students thus may learn the use of the words they get themselves more effectively pedagogically. The value of literature does not gial only insight of humanity, but that of values for learning the English language in the classroom. Although pedagogy is sometimes seen as a neubulos concept, it is essential a combination of knowledge and skills required for effective teaching.